Analysis of self-heating-related instability in n-channel low-temperature polysilicon TFTs with different S/D contact hole densities. (1st March 2022) - Tu, Yu-Fa; Chang, Ting-Chang; Zhou, Kuan-Ju; Hung, Yang-Hao; Zheng, Yu-Zhe; Chen, Jian-Jie; Tai, Mao-Chou; Wang, Yu-Xuan; Hung, Wei-Chun; Hung, Wei-Chieh; Lien, Chen-Hsin
Abstract: This study examines self-heating-related instability in n-channel low-temperature polysilicon thin-film transistors with different source/drain contact hole densities. Devices with more contact holes exhibit a higher on-current without additional parasitic capacitance, further enhancing the RC delay property. For high-current-induced self-heating stress, a device with one contact hole has one hump due to the kink effect. However, a device with six contact holes has two humps, induced by the kink effect and thermionic field emission. COMSOL simulations of heat distribution and energy bands are performed to examine the different degradation behaviors, and then physical models are proposed.